2018
DOI: 10.4236/jss.2018.610007
|View full text |Cite
|
Sign up to set email alerts
|

Major Causes of Acculturative Stress and Their Relations with Sociodemographic Factors and Depression among International Students

Abstract: The purpose of the study was to examine the main sources of acculturative stress and their associations with sociodemographic factors and depression. A descriptive cross-sectional research design was employed to investigate the study. International students (N = 506) volunteered to take part in the survey and completed two self-report questionnaires: Acculturative Stress for International Students Scale and a Center for Epidemiological Studies Depression Scale. Descriptive statistics, Pearson's product moment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…More specifically, the common challenges that international students encounter include language barriers, perceived discrimination, financial concerns, homesickness, academic pressure and culture shock [12] [13] [14]. Similarly, several studies conducted among international students studying in China revealed that the students experienced mental health problems, such as stress and depression as a result of acculturative stressors [15] [16] [17]. In light of the psychological adjustment difficulties and their devastating impact on psychological well-being, numerous researchers have at- [9] [10] [25].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the common challenges that international students encounter include language barriers, perceived discrimination, financial concerns, homesickness, academic pressure and culture shock [12] [13] [14]. Similarly, several studies conducted among international students studying in China revealed that the students experienced mental health problems, such as stress and depression as a result of acculturative stressors [15] [16] [17]. In light of the psychological adjustment difficulties and their devastating impact on psychological well-being, numerous researchers have at- [9] [10] [25].…”
Section: Introductionmentioning
confidence: 99%
“…Może to wynikać także głównie z samej migracji, szczególnie w kontekście uchodźców. Stres akulturacyjny -emocjonalna reakcja na zmianę w kulturze pobytu związana z wieloma stresorami (Berry, 1997) -często powoduje wyuczoną bezradność i wyuczoną zależność, depresję, lęk, niższą samoocenę, problemy z tożsamością i utratę autonomii (Boekestijn, 1988;Telzer, Vazquez, 2009;Gembala, 2010;Kubitsky, 2012;Gebregergis, 2018). Wszystko to zabiera sprawczość osób migrujących.…”
Section: Wyzwania Stojące Przed Pedagogami Społecznymi Pracującymi Z Migrantamiunclassified
“…It can mainly results from migration itself, especially in the context of refugees. Acculturative stress -an emotional response to a change in the culture of residence connected to many stressors 8 (Berry, 1997: 30) -often causes learned helplessness and leaned dependency, depression, anxiety, lower self-esteem, identity problems and loss of autonomy (Boekestijn, 1988;Telzer, Vazquez, 2009;Gembala, 2010;Kubitsky, 2012;Gebregergis, 2018). All this take away migrants' agency.…”
Section: Challenges In Front Of Social Pedagogues Working With Migrantsmentioning
confidence: 99%
“… John Berry (1997) described four acculturation strategies -marginalization, separation, assimilation and integration.8 There are number of significant stressors that are likely to be pervasive, intense, and lifelong such as: cultural shock (new and different laws, values, traditions, ways of behavior, cuisine), language, financial issues, discrimination, alienation and isolation, homesick(Gebregergis, 2018).…”
mentioning
confidence: 99%